Numerical Simulation of Rotary Compression Process of Hollow Balls - Skrochocki, D.; Tomczak, J. (Проблемы прочности, 2016)
This paper presents results of the analysis of numerical Simulation of rotary compression process of hollow ball forging. Numerical analysis is conducted based on the finite element method using the Simufact Forming software. The methods of hollow ball forming are discussed with presentation of the geometrical model applied in calculations and the obtained rotary compression process description. The simulation is conducted under three-dimensional strain conditions. Strain, stress and temperature distributions are determined. The diagrams of forces and rotary moments of the hollow forging compression process are given. The described results of the numerical analysis confirm the possibility of producing the hollow balls by means of rotary compression with the use of billet in the form of a pipe part.